Reading Women Participations on Populism Politics - Marwah, Sofa (Political Science Program, Universitas Negeri Semarang, 2019)
This paper aims to elaborate on women participation on politic populist development and expansion of support by the strength of women's groups as representatives of civil society. This study uses literature study methods to discover various data related to women's figures and women's group dedication in the context of civil society, sourced from journal and preliminary study results. The results of the study indicate that women participate in the practice of populism associated with men in cultivating the issues of populism and are received by the general public. Even women's contribution to society tends to be closer to welfare issues that are echoed in populist politics. When the populism politics need to expand in the context of the wider society, women are also present and have been there for a long time dedicating their lives on social welfare issues. The implication, it is necessary to see women contributions are as important as men in the practice of populist politics, not only at the level of the political elite but also in the life of the wide society. Women's groups are able to fill spaces that are not filled by the state, i.e. socio-economic spaces, wherever women are.